Life cycle assessment of mortars: A review on technical potential and drawbacks. (21st June 2021) - Santos, T.; Almeida, J.; Silvestre, J.D.; Faria, P.
Highlights: Mortars sustainability was reviewed through a life cycle assessment (LCA) approach. Results normalization improved the feasibility to compare diverse LCA studies. Global warming potential category is strongly affected during mortars production. Conventional binders' replacement by secondary resources alleviates mortars impacts. Abstract: The in-depth research on efficient processes and alternative constituents for mortars production has a lack on the quantification of their environmental impacts. This work presents a critical review of life cycle assessment (LCA) studies performed in the construction sector, namely related to mortars. The gaps and barriers of these methods and final results are discussed through an overview of the main achievements on mortars' environmental life cycle studies in Europe. Despite the future trends, LCA studies are more focused on cement-mortars and few researches on air lime, gypsum or earth mortar binders are reported in the literature.